Comparative morphology analysis of live blood platelets using scanning ion conductance and robotic dark-field microscopy. (17th August 2016) - Kraus, Max-Joseph; Seifert, Jan; Strasser, Erwin F.; Gawaz, Meinrad; Schäffer, Tilman E.; Rheinlaender, Johannes
Abstract: Many conventional microscopy techniques for investigating platelet morphology such as electron or fluorescence microscopy require highly invasive treatment of the platelets such as fixation, drying and metal coating or staining. Here, we present two unique but entirely different microscopy techniques for direct morphology analysis of live, unstained platelets: scanning ion conductance microscopy (SICM) and robotic dark-field microscopy (RDM). We demonstrate that both techniques allow for a quantitative evaluation of the morphological features of live adherent platelets. We show that their morphology can be quantified by both techniques using the same geometric parameters and therefore can be directly compared. By imaging the same identical platelets subsequently with SICM and RDM, we found that area, perimeter and circularity of the platelets are directly correlated between SICM and dark-field microscopy (DM), while the fractal dimension (FD) differed between the two microscopy techniques. We show that SICM and RDM are both valuable tools for the ex vivo investigation of the morphology of live platelets, which might contribute to new insights into the physiological and pathophysiological role of platelet spreading.